THE MODERN CONDITION OF FISH FARMING, THE HISTORY AND DEVELOPMENT OF THE INDUSTRY IN POLTAVA REGION - Усачова, В. Є. (Scientific Progress & Innovations, 2015)
Fish production in the segment of world aquaculture are studied and based on the literature. The fish catching and production of other aquatic resources in Ukraine and Poltava region in the last years is analyzed. The some aspects of the historical development of fish farming in the region are considered. The potential of the fishing industry in the study area is clarified. That is defined by the presence of a complex of conditions for its development, including a large number of fisheries waters, a system of pond farms.